Synthesis and self-assembly of biodegradable polyethylene glycol-poly (lactic acid) diblock copolymers as polymersomes for preparation of sustained release system of doxorubicin - Alibolandi, Mona; Sadeghi, Fatemeh; Sazmand, Seyed Hossein; Shahrokhi, Seyed Mohammad; Seifi, Mahmoud; Hadizadeh, Farzin (International Journal of Pharmaceutical Investigation)
Introduction: The copolymer of polyethylene glycol (PEG) and polyesters has many interesting properties, such as amphiphilicity, biocompatibility, biodegradability, and self-assembly in an aqueous environment. Diblock copolymers of PEG-polyester can form different structures such as micelles, polymersome, capsules or micro-container in an aqueous environment according to the length of their blocks. Materials and Methods: Herein, a series of poly (lactic acid) (PLA) and PEG diblock copolymers were synthesized through the ring-opening polymerization. The polymerization reaction and the copolymer structures were evaluated by nuclear magnetic resonance (NMR) and gel permeation chromatography (GPC). The corresponding copolymers were implemented for the formation of polymersome structures using fi lm rehydration method. Impact of methoxy PEG chain length and hydrophobic weight fraction on particle size of polymersomes were studied, and the proper ones were selected for loading of doxorubicin (DOX) via pH gradient method. Results and Discussion: Results obtained from 1HNMR and GPC revealed that microwave irradiation is a simple and reliable method for the synthesis of PEG-PLA copolymers. Further analysis indicated the copolymer with relative molecular weight of PLA to PEG ratios of 3 or fEo ~ 25% produced the smallest size polymersomes. Polymersomes prepared from PEG5000 to PLA15000 were more capable in loading and sustained release of DOX than those prepared from PEG2000 to PLA6000. Conclusion: In conclusion copolymers of PEG/PLA with fOE ~25% and relatively higher molecular weight are more suitable for encapsulation and providing sustained release of DOX.
Keywords: Copolymer; doxorubicin; polyethylene glycol-poly (lactic acid); polymersome; self- assembly